1982
DOI: 10.1289/ehp.824541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phthalate esters on lipid metabolism in various tissues, cells and organelles in mammals.

Abstract: The effect of phthalate ester plasticizers on a variety of enzyme systems was studied in rats, rabbits and pigs. The feeding of di(2-ethylhexyl) phthalate (DEHP) to animals at levels from 0.1% to 1.0% in the diet resulted in diverse biochemical effects, such as inhibition of cholesterologenesis in liver, testes, and adrenal gland; inhibition of cholesterologenesis in brain and liver of fetal rats from DEHP-fed dams; decreased plasma cholesterol levels; decreased synthesis of hepatic phospholipid and triglyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 73 publications
3
20
0
Order By: Relevance
“…The objectives of this investigation were to assess the sensitivity of sexually mature rats to the toxic responses induced by the dietary administration of DEHP, to examine the reproductive performance of male rats following exposure to the gonadotoxic and subgonadotoxic dose levels, and to observe the patterns of recovery from toxicity upon the discontinuance of exposure to DEHP Dietary administration of DEHP in the present study produced phthalate ester characteristic toxicity in rats as indicated by reduced body weight gain, reduced testicular and accessory sex-organ weights, loss oftesticular zinc, induction of seminiferous tubular atrophy, lowered serum triglycerides and cholesterol, and hepatomegaly (5)(6)(7)16,17). The toxic response to DEHP was dose-dependent and statistically significant with varying severities depending upon the target tissue.…”
Section: Discussionmentioning
confidence: 91%
“…The objectives of this investigation were to assess the sensitivity of sexually mature rats to the toxic responses induced by the dietary administration of DEHP, to examine the reproductive performance of male rats following exposure to the gonadotoxic and subgonadotoxic dose levels, and to observe the patterns of recovery from toxicity upon the discontinuance of exposure to DEHP Dietary administration of DEHP in the present study produced phthalate ester characteristic toxicity in rats as indicated by reduced body weight gain, reduced testicular and accessory sex-organ weights, loss oftesticular zinc, induction of seminiferous tubular atrophy, lowered serum triglycerides and cholesterol, and hepatomegaly (5)(6)(7)16,17). The toxic response to DEHP was dose-dependent and statistically significant with varying severities depending upon the target tissue.…”
Section: Discussionmentioning
confidence: 91%
“…Diethyl and dibutyl phthalate also modify the action of drug-metabolizing enzymes (22)(23)(24) but not glucose-6-phosphatase activity (24). Dibutyl phthalate, like DEHP, is reported to lower plasma cholesterol and inhibit cholesterogenesis (25,26), while diethyl phthalate, like DEHP, lowers plasma triglyceride but unlike DEHP does not affect hepatic peroxisomes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 66(9): 1119-1124, 2004 The exposure of animals to phthalate esters can result in a significant perturbation of normal lipid metabolism in liver, heart, testis, adrenal gland and brain [4]. The plasticizer, di-(2-ethylhexyl) phthalate (DEHP), is a widespread environmental chemical due to its common use in the production of plastic medical devices and food packaging.…”
mentioning
confidence: 99%